Nomophobia: A Study to Evaluate Mobile Phone Dependence and Impact of Cell Phone on Health - Dongre, Ashwini S; Inamdar, Ismail F; Gattani, Prakash L (National Journal of Community Medicine, 2017)
Background: “Nomophobia” is the modern fear of being unable to communicate through a mobile phone. Itis important to understand how its use affects people’s well-being,and the consequences of having the device takenfrom frequent users. The present study was designed to study the prevalence of nomophobia, dependence pattern and health effects of mobile phone usage. Objective: The objectives were to study the prevalence of nomophobia among mobile phone users; to study cell phone dependence pattern among adults; and to study the health effects of mobile phone usage. Methodology: This was a community based cross sectional exploratory study conducted during 1st December 2015 to 1st May 2016. Results: Most of the subjects were in the age group of 16 – 20 years. The prevalence of nomophobiain the study was 68.92%. A higher proportion of males (82.91%) were dependent on mobile phone compared to females (31.25%). The most common self-perceived symptom due to increase mobile phone usage was lack of sleep (70.61%) followed by eyestrain (42.46%). Conclusion: Prevention is better than cure, most of the subject using mobile phone belong to younger age group therefore health education strategies should be targeted to youth to prevent harmful effect of this great invention.